Synthesis and characterization of microcrystalline cellulose produced from bacterial cellulose - de Oliveira, Rafael Leite [UNESP]; Barud, Hernane da Silva [UNESP]; de Assuncao, Rosana M. N.; Meireles, Carla da Silva; Carvalho, Geandre Oliveira; Rodrigues Filho, Guimes; Messaddeq, Younes [UNESP]; Lima Ribeiro, Sidney Jose [UNESP] (Springer, 2011)
In this study, microcrystalline cellulose (MCC) was prepared from the acid hydrolysis of bacterial cellulose (BC) produced in culture medium of static Acetobacter xylinum. The MCC-BC produced an average particle size between 70 and 90 mu m and a degree of polymerization (DP) of 250. The characterization of samples was performed by thermogravimetric analysis, X-ray diffraction, and scanning electron microscopy (SEM). The MCC shows a lower thermal stability than the pristine cellulose, which was expected due to the decrease in the DP during the hydrolysis process. In addition, from X-ray diffractograms, we observed a change in the crystalline structure. The images of SEM for the BC and MCC show clear differences with modifications of BC fiber structure and production of particles with characteristics similar to commercial MCC.
Keywords: Bacterial cellulose; Microcrystalline cellulose; Acetobacter xylinum; Acid hydrolysis